The cultural cold war the CIA and the world of arts and letters - Saunders, Frances Stonor 1966- (The New Press, 2013)
"During the Cold War, freedom of expression was vaunted as liberal democracy’s most cherished possession—but such freedom was put in service of a hidden agenda. In The Cultural Cold War, Frances Stonor Saunders reveals the extraordinary efforts of a secret campaign in which some of the most vocal exponents of intellectual freedom in the West were working for or subsidized by the CIA—whether they knew it or not. Called "the most comprehensive account yet of the [CIA’s] activities between 1947 and 1967" by the New York Times, the book presents shocking evidence of the CIA’s undercover program of cultural interventions in Western Europe and at home, drawing together declassified documents and exclusive interviews to expose the CIA’s astonishing campaign to deploy the likes of Hannah Arendt, Isaiah Berlin, Leonard Bernstein, Robert Lowell, George Orwell, and Jackson Pollock as weapons in the Cold War. Translated into ten languages, this classic work—now with a new preface by the author—is "a real contribution to popular understanding of the postwar period" (The Wall Street Journal), and its story of covert cultural efforts to win hearts and minds continues to be relevant today." Klappentext
Originally published: Who paid the piper?, London: Granta Books, 1999
Keywords: USA -- Central Intelligence Agency; International Association for Cultural Freedom; Geschichte 1947-1967; Propaganda; Kulturpolitik; Ost-West-Konflikt